‘We Poles are pill poppers’: Proximity in Polish medical popularisation videos on YouTube - Tereszkiewicz, Anna; Szczyrbak, Magdalena (Ibérica (Castellón de la Plana, Spain), 2022)
The paper focuses on strategies of creating proximity in multimodal online communication. Based on the case study of a popular Polish YouTube medical channel (i.e. Najprościej mówiąc), the analysis examined how, relying on different modes of communication, the authors establish a relationship with the audience and how they create and display their identity and their position on the issues discussed. It was also the aim to determine whether the socio-cultural context of communication and the national identity of the YouTubers influences the construction of proximity. To uncover these aspects the study drew on the concept of proximity as introduced and defined by Hyland (2010). The results show a diversity of multimodal strategies of establishing proximity along five facets of organisation, argument, credibility, stance, and engagement. The original classification into the proximities of commitment and membership was extended to include a third type, i.e. the proximity of experience, which involves the demonstration of communality with and knowledge of the immediate socio-cultural context of communication.